An Improved PSFB PWM DC-DC Converter for High-Power and Frequency Applications - Bakan, A. Faruk; Altintas, Nihan; Aksoy, Ismail (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2013)
In the phase shifted full bridge (PSFB) pulse width modulation(PWM) converter, external snubber capacitors are connected in parallel to insulated gate bipolar transistors (IGBTs) in order to decrease turn-off losses. The zero voltage transition (ZVT) condition is not provided at light loads, thus the parallel capacitors discharge through IGBTs at turn on which causes switching losses and failure risk of the IGBTs. Capacitor discharge through IGBT restricts the use of high-value snubber capacitors, and turn-off loss of the IGBT increases at high currents. This problematic condition occurs especially at the lagging leg. In this study, a new technique enabling the use of high-value snubber capacitors with the lagging leg of the PSFB PWM converter is proposed. As advantages of the proposed technique, high-capacitive discharge current through IGBT is prevented at light loads, the turn-off switching losses of the IGBTs are decreased, and the performance of the converter is improved at high currents. The proposed PSFB PWM converter includes an auxiliary circuit, and it has a simple structure, low cost, and ease of control as well. The operation principle and detailed design procedure of the converter are presented. The theoretical analysis is verified exactly by a prototype of 75 kHz and 10kW converter.
Keywords: DC-DC converters; phase shifted full bridge (PSFB) PWM converter; soft switching; zero voltage switching (ZVS); FULL-BRIDGE CONVERTER; ZERO-VOLTAGE; DESIGN; SERIES; Engineering